Geometric Characterization of the Numerical Range of Parallel Sum of Two Orthogonal Projections - Weiyan Yu; Ran Wang; Chen Zhang (Journal of Mathematics)
Let H be a complex separable Hilbert space and BH be the algebra of all bounded linear operators from H to H. Our goal in this article is to describe the closure of numerical range of parallel sum operator P:PQ for two orthogonal projections P and Q in BH as a closed convex hull of some explicit ellipses parameterized by points in the spectrum.